Interactions between Neutrophils, Th17 Cells, and Chemokines during the Initiation of Experimental Model of Multiple Sclerosis - Dagmara Weronika Wojkowska; Piotr Szpakowski; Dominika Ksiazek-Winiarek; Marcin Leszczynski; Andrzej Glabinski (Hindawi Limited, 2014)
Experimental autoimmune encephalomyelitis (EAE) is an animal model of multiple sclerosis (MS) in which activated T cell and neutrophil interactions lead to neuroinflammation. In this study the expression of CCR6, CXCR2, and CXCR6 in Th17 cells and neutrophils migrating to the brain during EAE was measured, alongside an evaluation of the production of IL-17, IL-23, CCL-20, and CXCL16 in the brain. Next, inflammatory cell subpopulations accumulating in the brain after intracerebral injections of IL-17 or CXCL1, as well as during modulation of EAE with anti-IL-23R or anti-CXCR2 antibodies, were analyzed. Th17 cells upregulate CXCR2 during the preclinical phase of EAE and a significant migration of these cells to the brain was observed. Neutrophils upregulated CCR6, CXCR2, and CXCR6 during EAE, accumulating in the brain both prior to and during acute EAE attacks. Production of IL-17, IL-23, CCL20, and CXCL16 in the CNS was increased during both preclinical and acute EAE. Intracerebral delivery of CXCL1 stimulated the early accumulation of neutrophils in normal and preclinical EAE brains but reduced the migration of Th17 cells to the brain during the preclinical stage of EAE. Modulation of EAE by anti-IL-23R antibodies ameliorated EAE by decreasing the intracerebral accumulation of Th17 cells.